COMPARISON OF CBCT AND CT IN TERMS OF DOSE VALUE OF ORGANS AT RISK IN PARANASAL SINUS IMAGING. Issue 4 (7th March 2022) - Pak, Farideh; Hosseini Pooya, Seyed Mahdi; Shabani, Hamed; Baradaran, Samaneh; Salim Sadeq, Ula
Abstract: Irradiated dose to the organs at risk surrounding the paranasal sinuses was compared in cone beam computed tomography (CBCT) and multi spiral computed tomography with respect to the organs' relative positions to the imaging field. A head and neck Alderson-Rando phantom equipped with thermoluminescence dosemeters pellets was irradiated according to three routine CBCT protocols and one protocol in multi spiral computed tomography. Dose value of organs outside the imaging field as well as those measured dose of organs inside the field were assessed. The highest measured doses were obtained from CT scan for most of the organs investigated in this study, whereas the lowest one was associated with the low-resolution mode of CBCT. Also, statistical analysis showed no significant differences between the dose values of out-of-field organs in all CBCT modes, whereas significant differences were observed between the radiation doses of CT and CBCT modes for all organs at risk inside and outside of the imaging field. CBCT is recommended on the basis of having a lower dose; however, the image qualities were the same in the two employed modalities, so the approach of lower dose can be made.